Job commitment and work attitudes among librarians of universities in Western Visayas and their implications to efficiency and effectiveness - Linaugo, Analiza G. (2009)
This study aimed at determining the job commitment and work attitude of librarians in universities in Western Visayas and their implications to efficient and effective library service. Specifically, it sought to find the following about the librarians: their profile according to age, civil status, length of service, type of institution, educational qualification, and educational attainment; the extent of their job commitment; the prevailing work attitude; the level of their efficiency and effectiveness based on the perception of their immediate unit head or administrators, their peers, and themselves; and the significant relationship between 1) the librarians' job commitment and their age, civil status, length of service, type of institution, educational qualification, and educational attainment; 2) the librarians' job commitment and work attitude; 3) the librarians' job commitment and their efficiency and effectiveness; 4) the librarians' work attitude and their age, civil status, length of service, type of institution, educational qualification, and educational attainment; and 5) the librarians' work attitude and their efficiency and effectiveness.